Kırâat ilminde usûle dâir üç mesele : istiᶜâze, besmele ve idgâm - Temel, Enes (My University, 2014)
1.ÖZET Kırâat ilmi, bizzat Kur'ân-ı Kerîm’in lafzını ele alması nedeniyle İslamî ilimlerin en üstünü olarak görülmüştür. Kırâat farklılıklarından dolayı lafızlarda oluşan değişikliklerin kimi zaman mana farklılıklarına yol açması da Kırâat ilmini, diğer İslamî ilimler için vazgeçilmez bir başvuru kaynağı haline getirmiştir. Peygamberimiz (s.a.s) döneminden itibaren bu ilme büyük önem verilmiş ve yüzlerce eser te’lif edilmiştir. İslamî ilimlerden tefsir, hadis ve fıkıh’da olduğu gibi kırâat ilminde de bütün vecihlerin teker teker incelendiği ferş konularının yanında, bu konuların incelenmesine yardımcı olacak usûl konuları bulunmaktadır. Işte bu usûl konuları ile ilgili te’lif edilen kitaplardaki konular arasında genelde ilk üç sırada istiᶜâze, besmele ve idgâm bulunmaktadır. Bu sıralamanın oluşmasında esas alınan prensip, Kur'ân-ı Kerîm’deki âyetlerin sıralamasıdır. Bu durumda da istiᶜâze ve besmele’nin ilk planda yer alacağı âşikârdır. İdgâm konusu ise sıralama itibariyle ilk sûre olan Fâtihâ’nın ikinci âyetinde yer alan “مَالِكِ الرَّحِيمِ” ifadesi nedeniyle üçüncü konu olmuştur. İşte bu çalışma da üç konuyu, farklı ilim dallarındaki ele alınışını da göz önünde bulundurarak işlemeye yöneliktir. Kırâat, Usûl, Fonetik (Asvât), İstiᶜâze, Besmele, İdgâm, İdgâm-ı Kamil, İdgâm-ı Nakıs, İzhâr, İklâb, İhfâ, Nûn-u Sâkin, Tenvîn, 1.

The scholarship of reading has been supposed to be the superlative one among the Islamic sciences due to its investigation of Koran’s wording. The fact that the changes, come into existence in the wordings because of reading differences, cause meaning differences has made the scholarship of reading an indispensable reference guide for the Islamic sciences. A great importance has been given to this scholarship since the era of Prophet Mohammad (PbuH). Besides the fersh subjects by which the whole angles are investigated one by one in interpretation, hadith and fiqh from Islamic sciences as well as the scholarship of reading, there are method subjects which will help to investigate these subjects. In general, istiᶜaza, basmala and idgam take place in the first three subjects among the subjects in the books compiled in concern with aforementioned method subjects. The reason based on during the formation of this ordering is the orderings of verses in Koran. Therefore, it’s obvious that istiaza and basmala will take place in the first plan. The subject of idgam is the third subject by the reason of the expression “مَالِكِ الرَّحِيمِ” which is taken place in the second verse of Surah al-Fâtihâ being the first surah by ordering. This study is devoted to examine these three subjects by taking into consideration its being discussed in different science branches. Key Words : Qıra’at, Methodology, Phonetics(pronunciation), Istiazah(Taking Refuge to Allah), Basmala, Al-Ith-haar, Al-Idghaam, Al-Iqlaab, Al-Ikhfaa’, Ghunnah, Noon Saakinah, Tanween,
Keywords: İslam Dini; Kur’an-ı Kerim; Tefsir